Faktor-faktor yang Mempengaruhi Kepuasan Pengguna Sistem Informasi Akuntansi di Shopee Paylater - Arif Farida; Kun Ismawati; Handayani Tri Wijayanti (Riset Manajemen dan Akuntansi, 2025)
Satisfaction in using the Accounting Information System (AIS) in Shopee PayLater is influenced by several factors, including Perceived Usefulness, Perceived Ease of Use, and Information System Quality. The purpose of this study is to examine the effect of these variables on user satisfaction of the Accounting Information System (AIS) in Shopee PayLater (SPayLater). This study uses primary data collected through questionnaires. The research method applied is a quantitative approach, with a sample of 40 respondents who have used SPayLater in the city of Surakarta. Hypothesis testing was conducted using SPSS Version 25 software. The results of this study indicate that only the Information System Quality variable has a significant effect on user satisfaction of the Accounting Information System in SPayLater.